Regional Integration in the Black Sea Region: the Case of Two Sisters, Istanbul and Odessa - Gulden Erkut; Mete Basar Baypinar (European Regional Science Association (ERSA), 2006)
The political change in the 1980'es and 1990'es in the Black Sea Region has introduced many questions regarding its future as the region faces massive problems like conflicts on territory, drop of production levels in the 1990'es and related poverty, and last but not the least, environmental problems. The size of the region also blurs the picture. However, briefly there are three major influences that mark the future development of the region: globalization, regionalization and Euro-Asian integration. We propose that under these three influences, a new global integration zone, consisting of multiple networks between cities of the Black Sea Region is emerging. Our proposition that a new global integration zone is emerging within the Black Sea Region depends on three assumptions: Our first assumption is that neo-liberal globalization and regionalization (and particularly Euro-Asian integration) lead to development of similar political changes in the region. Our second assumption is that neo-liberal globalization and regionalization lead to development of similar spatial socio-economic developments within the Black Sea Region which brings some cities to the fore to gain power in the national and global organization of production. Our third assumption is that there is increasing trans-national integration between subject cities. Emergence of such a zone is perhaps most important for policy makers at the local level who have to face either positive or negative on-site effects of globalization and regionalization. Increasing socio-economic inequalities, excessive agglomeration of economic activities and population, diversification of population and increasing complexity of problems cripple traditional city management and planning practices in these countries which have a strong central planning and administration background. Due to practical reasons, we limit our study to integration of two sub-national regions, the province of Istanbul, and the province of Odessa which are also sister cities. Province of Istanbul may be recalled as Greater Istanbul, or Istanbul Metropolitan City since at 2004 due to change in the administrative legislation. Province of Odessa includes the city of Odessa as well as other cities within the province. We may conclude that there is progressive convergence in the political grounds between Turkey-Ukraine and Istanbul-Odessa, mainly in the framework of the global structures that are predominantly part of the Euro-Atlantic supra-structure. Though there is not much evidence of similarity in spatial development of Istanbul and Odessa, particularly due to political inclarity and problems of administrative decentralization in Ukraine, there is evidence of economic and social integration, between Turkey-Ukraine and Istanbul-Odessa, which experiences slow development, and negative side effects like informal activities. As a conclusion we may argue that integration of two regions might heavily depend on the Ukrainian foreign and domestic policies, and the decisions of supra-national structures like the World Trade Organization and EU. We may expect a progress in economic integration by the removal of trade barriers, where Istanbul and Odessa would be direct beneficiaries as both production and transfer centres. Further administrative decentralization in Ukraine might lead to a re-population in Odessa Region, as happened in Istanbul after the 1980 period.
Keywords: 330